DIGITAL-BASED HUMAN RESOURCE MANAGEMENT TRANSFORMATION IN ENHANCING EMPLOYEE PERFORMANCE AND ENGAGEMENT IN THE ERA OF FLEXIBLE WORK - Achmad Mohyi (Yayasan Adra Karima Hubbi, 2026)
Digital transformation in human resource management (HRM) has become a strategic issue alongside the expansion of flexible work arrangements and the growing performance demands placed on public sector organizations. This shift requires organizations not merely to adopt technology for administrative purposes, but also to ensure that HRM digitalization contributes sustainably to employee productivity and job satisfaction. This study aims to examine the effect of digital HRM transformation on employee work productivity and job satisfaction, as well as to explain the underlying mechanisms of this relationship through the lenses of the Ability–Motivation–Opportunity (AMO) framework and Self-Determination Theory (SDT). The study employed a quantitative approach using a survey design. The research sample consisted of 98 employees from public service institutions in East Java, selected through quota random sampling to ensure adequate representation across work units. Data were collected using a five-point Likert-scale questionnaire and analyzed the results indicate that digital HRM transformation is perceived at a high level and has a positive and significant effect on both employee productivity and job satisfaction. These findings suggest that HRM digitalization strengthens employees’ abilities and work opportunities while simultaneously fulfilling basic psychological needs, namely autonomy, competence, and relatedness. The study concludes that strategically designed digital HRM transformation plays a critical role in enhancing employee performance and engagement, particularly within the context of flexible work arrangements in the public sector.